2021
DOI: 10.3390/brainsci11081090
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Effect of Sleepiness on Driving Performance: A Systematic-Review

Abstract: Background: Several studies highlighted that sleepiness affects driving abilities. In particular, road traffic injuries due to excessive daytime sleepiness are about 10–20%. Considering that aging is related to substantial sleep changes and the number of older adults with driving license is increasing, the current review aims to summarize recent studies on this issue. Further, we intend to provide insights for future research. Methods: From the 717 records screened, ten articles were selected and systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In a review of 10 driver sleepiness studies, Scarpelli et al [34] concluded that older drivers are less vulnerable to sleep loss and sleepiness-related driving impairments than young adults. For example, Campagne et al [35] compared the frequency of driving errors and the vigilance of older drivers (60-70 years) and younger drivers (20-30 years and 40-50 years) during long, monotonous night driving sessions in the simulator.…”
Section: Effects Of Fatigue Age and Gendermentioning
confidence: 99%
“…In a review of 10 driver sleepiness studies, Scarpelli et al [34] concluded that older drivers are less vulnerable to sleep loss and sleepiness-related driving impairments than young adults. For example, Campagne et al [35] compared the frequency of driving errors and the vigilance of older drivers (60-70 years) and younger drivers (20-30 years and 40-50 years) during long, monotonous night driving sessions in the simulator.…”
Section: Effects Of Fatigue Age and Gendermentioning
confidence: 99%
“…Sleepiness at the wheel should be specifically investigated, since the risk for car accidents is high in subjects reporting episodes of severe SW [25] and in patients with OSA [26]. Although elderly subjects often report sleepiness, the risk for a poor driving performance associated with sleepiness is lower in old adults compared to young adults, possibly because the former tend to avoid what they perceive as dangerous situations-for example, driving at night [27]. Conversely, risky driving behavior was associated with an increased risk for accidents [28].…”
Section: Epidemiology Of Driving Accidents In the General Population ...mentioning
confidence: 99%